Соціальна відповідальність бізнесу в Україні: сучасний стан та шляхи розвитку - Решетняк, Наталя Борисівна; Назаренко, Олена Василівна; Єгорова, Юлія Валеріївна (НТУ "ХПІ", 2018)
У статті досліджується соціальна відповідальність бізнесу як основа сталого розвитку національної економіки. Розглянуто переваги впровадження концепції соціальної відповідальності для компаній, суспільства і держави. Проаналізовано сучасний стан соціальної відповідальності бізнесу в Україні. Визначено наявні проблеми у розвитку соціальної відповідальності українського бізнесу. Наведено напрями реалізації соціальної відповідальності суб'єктами господарської діяльності. Вказано основні шляхи подальшого розвитку соціальної відповідальності бізнесу в Україні, які допоможуть залучити нові компанії до участі в ній.

The article studies the social responsibility of business as the basis of sustainable development of national economy. The advantages of introducing the concept of social responsibility have been considered for companies, society and the state. Social initiatives of individual Ukrainian companies have been studied. The modern state of social responsibility of business in Ukraine has been analyzed. The current problems in development of social responsibility of the Ukrainian business have been identified. The areas of implementation of social responsibility by business entities have been presented. The main ways of further development of social responsibility of business in Ukraine that will be able to attract new companies to participate in it have been specified.
Social responsibility of business in Ukraine: the modern state and ways of development
Keywords: компанія; сталий розвиток; стратегія; партнерство; співпраця; social responsibility; business; state; company; sustainable development; strategy; partnership; cooperation